2009
DOI: 10.3844/ajessp.2009.639.646
|View full text |Cite
|
Sign up to set email alerts
|

Co-Digestion of Palm Oil Mill Effluent and Refined Glycerin Wash Water for Chemical Oxygen Demand Removal and Methane Production

Abstract: Problem statement: Refined Glycerin Wash Water (RGWW) from the oleochemical industry contains high Chemical Oxygen Demand (COD) and requires proper treatment before disposal. Unfortunately the wash water also contains high concentration of sodium chloride (NaCl) that could cause inhibition to the normal biological treatment process. However, there is feasibility of co-digesting the RGWW and Palm Oil Mill Effluent (POME) for its treatment and methane recovery. Approach: A large 500 m3 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Since POME has currently little or no recycling value, it constitutes an environmental hazard, undergoing slow (acidic) degradation in pits from which it emits strong, foul odour causing air pollution and contamination of ground and surface waters and agricultural land besides vector attraction. Attempts have been made to achieve valorization of POME through production of microbial biomass, enzymes, energy, and biochemicals [27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Since POME has currently little or no recycling value, it constitutes an environmental hazard, undergoing slow (acidic) degradation in pits from which it emits strong, foul odour causing air pollution and contamination of ground and surface waters and agricultural land besides vector attraction. Attempts have been made to achieve valorization of POME through production of microbial biomass, enzymes, energy, and biochemicals [27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings also revealed that a 70:30 ratio of POME to cow manure could produce a methane content of 35.35% over 28 days of digestion [59]. POME has also been co-digested with other feedstock, such as empty fruit bunch (EFB), decanter cake, rumen fluid, and refined glycerine wash water [60][61][62][63].…”
Section: Co-digestionmentioning
confidence: 63%
“…Approximately 50% of the water utilized results in POME. For every ton of crude palm oil extracted from milling, about 2.5 tons of POME are generated (Sulaiman et al, 2009). Raw POME has a very high organic content and if discharged into receiving waterways, has the potential to cause adverse environmental consequences.…”
Section: Resultsmentioning
confidence: 99%